Efficacy and safety of antibody–drug conjugates in the treatment of urothelial cell carcinoma: a systematic review and meta-analysis of prospective clinical trials - Ren, Jun-Wei; Chen, Ze-Yu; Bai, Yun-Jin; Han, Ping (Frontiers in Pharmacology, 2024)
Introduction: Urothelial carcinoma (UC) is a refractory disease, and satisfactory outcomes are still challenging to achieve with current surgical interventions. Antibody-drug conjugates (ADCs), as a novel class of targeted therapeutics, have demonstrated encouraging results. While there is a limited number of high-quality randomized control trial (RCTs) examining the use of ADCs in patients with UC, some prospective nonrandomized studies of interventions (NRSI) provide valuable insights and pertinent information. We aim to assess the efficacy and safety of ADCs in patients with UC, particularly those with locally advanced and metastatic disease.Methods: A systematic search was conducted across PubMed, Embase, the Cochrane Library, and Web of Science databases to identify pertinent studies. Outcomes, such as overall response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), adverse events (AEs), and treatment-related adverse events (TRAEs) were extracted for further analysis.Results: Twelve studies involving 1311 patients were enrolled in this meta-analysis. In terms of tumor response, the pooled ORR and DCR were 40% and 74%, respectively. Regarding survival analysis, the pooled median PFS and OS were 5.66 months and 12.63 months, respectively. The pooled 6-months PFS and OS were 47% and 80% respectively. The pooled 1-year PFS and OS were 22% and 55% respectively. The most common TRAEs of ADCs were Alopecia (all grade: 45%